1998
DOI: 10.1055/s-2006-957494
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Diterpenoids Isolated fromBallota saxatilissubsp.saxatilis

Abstract: The genus Ballota L. (Lamiaceae) consists of about 33 species growing mainly in the Mediterranean region. In Turkey the genus Ballota is represented by eleven species, six subspecies, ten of which are endemic (1). Ballota saxatilis subsp. saxatilis Sieber ex J. & C. Presi. is distributed in Central Anatolia and has not been investigated before. The leaves and the tops of the plant are used for colic, asthma, influenza, insomnia, and haemorrhoids (2). The infusions prepared from the leaves are reported to posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 1 publication
0
29
0
Order By: Relevance
“…The Diels-Alder reaction of 4-phenyloxazole with 3-butyn-1-ol gave 2-(3-furyl)ethanol (18) in a yield of 61%. The methylenation of furan-3-carbaldehyde (16) [17] In our hands, it was rearranged and oxidized with PCC to hispanone (21) (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Diels-Alder reaction of 4-phenyloxazole with 3-butyn-1-ol gave 2-(3-furyl)ethanol (18) in a yield of 61%. The methylenation of furan-3-carbaldehyde (16) [17] In our hands, it was rearranged and oxidized with PCC to hispanone (21) (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] The synthesis of 11-nordrim-7-ene-2,9-dione (7) (Scheme 2) and 11-nordrim-7-en-9-one (15) has previously been described by Gesson et al [14,15] We used the monoprotected dione 8 for the first synthesis of the 2,7-functionalized bisnorlabdane (11). The vinyl ketone 15 represents an appropriate starting material for the synthesis of hispanone (21) (Scheme 1), a fungicidal and bactericidal furolabdane, which was first obtained by the transformation of hispanolone, [16,17] and has also been isolated from the plants Ballota saxatilis [18] (Lamiaceae) and Galeopsis angustifolia [19] (Labiatae).…”
Section: Introductionmentioning
confidence: 99%
“…Rajendhran et al, (1998) Citoglu et al, (1998) and Saha et al, (2013) reported inhibitory effect of medicinal plant extracts against Gram-positive and Gramnegative bacteria and few plant pathogenic fungi. Solvent extracts of Ocimum sanctum showed inhibited the growth of R. solanacearum (Murthy et al, 2014).…”
Section: Effect Of Ocimum Sanctum Extractmentioning
confidence: 99%
“…Ballota species have been used in Turkish folk medicine as antiulcer, antispasmodic, diuretic, choleretic, antihaemorrhoidal, and sedative agent (12)(13)(14)(15). Ballota L. is represented by 16 taxa in Turkey (16) ( Table 1).…”
Section: Monocytogenes Is Resistant To Different Environmental Conmentioning
confidence: 99%